ECOTOURISM DEVELOPMENT OF MUNJANG MANGROVE FOREST AND CONSERVATION EFFORTS BASED ON COMMUNITY APPROACH - Henri Henri; Seta Ardiawati (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2020)
Ecotourism development in a mangrove forest area includes many positive and negative aspects and requires a sustainablecomprehensive study. Ecotourism potential must be assessed to provide understanding of local people in managing natural resources. This study aims at identifying the potential for the development of ecotourism and determining the efforts of conservation strategies for supporting mangrove forests. Data collection was done by questionnaires and interviews using  1-5 Likert scale measurement and SWOT analysis to determine ecotourism development strategies. The results of the study indicates that Munjang mangrove forest has a very good potential to be developed as an ecotourism area. It is supported by the efforts of conservation as the main key in realizing the development of sustainable ecotourism. The role of the community and stakeholders has been well established such as mangrove seeding and nursery activities. Finally, this study recognizes that the capacity of sustainability indicators is very important to map the transformation and constant challenges of supporting mangrove ecotourism, so that it can provide conservation benefits, provide quality services for visitors and improve local communities welfare.